2021
DOI: 10.3389/fnhum.2021.666179
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Causal Inferences in Discourse Understanding and Logical Problem-Solving: A Meta-Analysis Study

Abstract: In discourse comprehension, we need to draw inferences to make sense of discourse. Previous neuroimaging studies have investigated the neural correlates of causal inferences in discourse understanding. However, these findings have been divergent, and how these types of inferences are related to causal inferences in logical problem-solving remains unclear. Using the activation likelihood estimation (ALE) approach, the current meta-analysis analyzed 19 experiments on causal inferences in discourse understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 116 publications
(171 reference statements)
1
5
0
Order By: Relevance
“…The framework considers message-level representations as probabilistically generating information at these multiple levels of representation. Other studies on language processing mainly investigated neurocognitive processing of prediction at multilevel representations in language comprehension with ERP and eye-tracking experiments ( Ryskin et al, 2019 ; Kuperberg et al, 2020 ; Leckey and Federmeier, 2020 ; Feng et al, 2021 ). Employing sentence reading tasks, Kuperberg et al (2020) examined whether the brain engaged different neurocognitive mechanisms in response to words (critical nouns in three-sentences scenarios) that confirmed and/or violated strong predictions at High constraint and Low constraint contexts during language comprehension among 39 native English speakers (mean = 21.6 years).…”
Section: Resultsmentioning
confidence: 99%
“…The framework considers message-level representations as probabilistically generating information at these multiple levels of representation. Other studies on language processing mainly investigated neurocognitive processing of prediction at multilevel representations in language comprehension with ERP and eye-tracking experiments ( Ryskin et al, 2019 ; Kuperberg et al, 2020 ; Leckey and Federmeier, 2020 ; Feng et al, 2021 ). Employing sentence reading tasks, Kuperberg et al (2020) examined whether the brain engaged different neurocognitive mechanisms in response to words (critical nouns in three-sentences scenarios) that confirmed and/or violated strong predictions at High constraint and Low constraint contexts during language comprehension among 39 native English speakers (mean = 21.6 years).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent neuroimaging studies have revealed that the existence of additional functions of LIPL, including attention, action and salience processing ( 32 36 ). Available literatures found that bilateral mPFC and LIPL jointly participant in the functions of emotional regulation, memory and executive function ( 37 39 ). Based on this discovery, it is reasonable to speculate that the decreased connectivity from mPFC to LIPL may be related to the injury of emotion, memory and executive function in T2DM patients and ultimately leading to the onset of cognitive disorders, but further investigation will be required.…”
Section: Discussionmentioning
confidence: 99%
“…The extent connectivity of the aMTG with parietal-occipital was also much greater during abstract semantic processing, but this was not the case for connectivity with frontal areas. This finding was unexpected given that the anterior temporal cortex plays an important role in the processing of abstract concepts ( Hoffman et al, 2015 ), and the frontal anterior cingulate cortices important for higher cognitive functions, such as abstract reasoning ( Reverberi et al, 2005 ; Jung et al, 2022 ), problem solving ( Grossman et al, 2002 ; Newman et al, 2003 ; Cazalis et al, 2006 ; Feng et al, 2021 ), judgment and decision making ( Zysset et al, 2002 ; Cunningham et al, 2004 ; Beer et al, 2010 ; Zander et al, 2016 ), creativity ( Gonen-Yaacovi et al, 2013 ), the supervisory control of attention and intention ( Shallice and Burgess, 1996 ; Cohen et al, 1999 ), planning ( Goel and Grafman, 1995 ; Gonen-Yaacovi et al, 2013 ), goal-directed and generative action and cognition ( Cohen et al, 1999 ; Baldo et al, 2001 ; Reverberi et al, 2005 ). Accordingly, it would be reasonable to infer that the aMTG would be more extensively connected to frontal cortex when processing abstract words.…”
Section: Discussionmentioning
confidence: 99%